2012
DOI: 10.1097/01.sa.0000410631.09026.a4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Omalizumab (Anti-IgE) for Asthma in Inner-City Children

Abstract: BACKGROUND-Research has underscored the effects of exposure and sensitization to allergens on the severity of asthma in inner-city children. It has also revealed the limitations of environmental remediation and guidelines-based therapy in achieving greater disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 21 publications
1
62
0
1
Order By: Relevance
“…In fact, Omalizumab (Xolair®) is a recombinant DNA-derived humanized monoclonal antibody indicated as an add-on therapy in patients aged ≥ 6 years with severe persistent allergic asthma uncontrolled at treatment step 4 or 5 according to guidelines GINA (2). Omalizumab demonstrated to be efficacious both in adults and children (3)(4)(5). In particular, in real-life studies, anti-IgE therapy showed short-and long-term benefits in terms of improving lung function and quality of life, achieving asthma control and reducing symptomatology, severe exacerbations, healthcare resource utilizations, hospitalizations, emergency department visits and reducing or discontinuing other asthma medications thus confirming, complementing, and extending evidence from randomized trials (3,5).…”
Section: Introductionmentioning
confidence: 67%
“…In fact, Omalizumab (Xolair®) is a recombinant DNA-derived humanized monoclonal antibody indicated as an add-on therapy in patients aged ≥ 6 years with severe persistent allergic asthma uncontrolled at treatment step 4 or 5 according to guidelines GINA (2). Omalizumab demonstrated to be efficacious both in adults and children (3)(4)(5). In particular, in real-life studies, anti-IgE therapy showed short-and long-term benefits in terms of improving lung function and quality of life, achieving asthma control and reducing symptomatology, severe exacerbations, healthcare resource utilizations, hospitalizations, emergency department visits and reducing or discontinuing other asthma medications thus confirming, complementing, and extending evidence from randomized trials (3,5).…”
Section: Introductionmentioning
confidence: 67%
“…Severity classification based on medication equivalents for alternative inhaled steroids was established using previous pediatric asthma studies. 25 Institutional review board approval was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Others have shown that 45% of inner-city children with moderate to severe asthma are exposed to mold and 50% to cockroaches (15,21). Routine allergy testing (22), medication changes or addition of allergen-specific immunotherapy (23,24), and public health interventions to assess in-home allergen exposure and reduce or remediate exposures that are found all have the potential to reduce asthma morbidity among high-risk patients (25)(26)(27).…”
mentioning
confidence: 99%